Preface - van Mensch, Peter (Acta Museologica Lithuanica, 2013)
With its about 110 museums taking care of about 6.5 million objects, Lithuania can be proud to have an adequate and varied museum provision. This does not mean that the situation is fully satisfactory. The post-1990 transition period has still left some issues unresolved, one of them being the perception of the social role of museums by the responsible authorities and the financing of museums accordingly. Based on a thorough analysis of Lithuanian museums, the present study takes a clear position about the potential of museums as public memory institutions in an informatikon society. [...]